Evaluation of The Program Facilitating Production Facilities/Infrastructure for Industrial Entrepreneurs in DKI Jakarta Using The Propensity Score Matching Method - Tri Ramdhani; Widyono Soetjipto (Publikasi Indonesia, 2026)
MSMEs have a central role in boosting Jakarta's economy, so policies that support competitiveness and productivity need to be prioritized. This study assesses the effectiveness of the New Industrial Entrepreneurship Program (WUIB) which is part of the Integrated Entrepreneurship Development (PKT). Referring to the theory of production function, this study designed a quasi-experimental approach using Propensity Score Matching on thousands of business actors in the culinary and craft/fashion sectors to compare recipients of the WUIB program who received production facilities accompanied by technical training with non-recipient business actors. The results of empirical analysis show that facility recipients experience a significant increase in turnover of Rp10-16 million per year. This effect is consistent across model specifications and passes validity and robustness tests across various matching algorithms, indicating that policy interventions are effective. The impact is short-term but shows a multiplier effect that strengthens regional economic activity. The study also highlights the mitigation of limitations through the identification of potential spillover to actors outside the target group, limitations of cross-sectional design that limits long-term inference and potential interference of marketing programs, mentoring, financial reporting facilitation and capital facilitation as a series of CCP programs. The results of the socio-economic analysis emphasized the broad benefits for women-led MSMEs, for those expanding their workforce capacity, and for actors with a primary-secondary education background. These findings encourage policymakers to expand and continue the program as part of the CCP strengthening strategy with data-based targeting, as well as improving turnover-based performance monitoring through an integrated information.